Analisis Perbandingan Profitabilitas Bank Syariah BUMN Sebelum dan Sesudah Merger Menjadi Bank Syariah Indonesia - Anisa Nurjanah; Djoni Djatnika; Iwan Setiawan; Kristianingsih Kristianingsih (Journal of Applied Islamic Economics and Finance, 2023)
This study is entitled Comparative Analysis of the Profitability of State-Owned Sharia Banks Before and After the Merger to Become a Bank Syariah Indonesia (BSI). The purpose of this study is to determine whether there is a difference in the profitability of the three BUMN Syariah Banks, namely BRI Syariah, BNI Syariah, and Bank Syariah Mandiri, 1 year before the merger, namely 2020 to 1 year after the merger, namely in 2021. The type of data used in this study is secondary data sourced from the financial statements of BRI Syariah, BNI Syariah, Bank Syariah Mandiri, and Bank Syariah Indonesia, with a quarterly timeline from 2020-2021. The method used in this study is the normality test and the different tests using the Independent Simple T-Test for normally distributed data and the Mann-Whitney U test for data not normally distributed. The results obtained from this study are that there is a difference in Gross Profit Margin between BRI Syariah, Bank Syariah Mandiri, and the average of the three state-owned Islamic banks 1 year before the merger and 1 year after the merger (when it has become a Bank Syariah Indonesia). At the same time, between BNI Syariah with Bank Syariah Indonesia, there is no difference. Likewise, with Net Profit Margin, there is a difference in Net Profit Margin between BRI Syariah, Bank Syariah Mandiri, and the average of the three state-owned Islamic banks 1 year before the merger and 1 year after the merger (when it has become a Bank Syariah Indonesia), while between BNI Syariah and There is no difference between Islamic Banks in Indonesia. Furthermore, there is no difference in Return on Assets and Return on Equity between BRI Syariah, BNI Syariah, Bank Syariah Mandiri, and the average of the three state-owned Islamic banks is 1 year before the merger with 1 year after the merger (when it has become a Bank Syariah Indonesia).